FAKTOR-FAKTOR PENENTU HARGA SAHAM LQ45: LIQUIDITY, LEVERAGE, PROFITABILITY, DAN MARKET RATIO DI BEI - Amelia Anwar; Nurohmayni Putri (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2026)
This study aims to analyze the simultaneous and partial effects of Current Ratio (CR), Debt to Equity Ratio (DER), Return on Equity (ROE), Return on Asset (ROA), Net Profit Margin (NPM), Earning Per Share (EPS), and Price Earning Ratio (PER) on stock prices of companies listed in the LQ45 index on the Indonesia Stock Exchange during the period 2020–2024. The main issue addressed is the significant fluctuation of LQ45 stock prices during the post-pandemic economic recovery, along with the inconsistency of previous research that only examined partial financial ratios. This quantitative causal research employed a purposive sampling technique, resulting in 22 companies that consistently remained in the LQ45 index, presented complete annual financial reports, and were not financial sector firms. Secondary data consisting of annual financial statements and closing stock prices were analyzed using multiple linear regression after natural logarithm transformation, preceded by classical assumption tests. Hypothesis testing was conducted with the F-test (simultaneous) and t-test (partial) at a 5% significance level using SPSS version 26. The results indicate that the seven financial ratios simultaneously have a significant effect on stock prices. Partially, ROE, EPS, and PER show positive and significant effects, while CR, DER, ROA, and NPM exhibit negative and significant effects. This study concludes that LQ45 investors place greater emphasis on equity-based profitability efficiency and future earnings growth prospects rather than liquidity levels and overall asset profitability amid post-pandemic economic recovery